La incertidumbre de futuro y la estrategia empresarial (2019)
Enterprises’ strategic decision are oriente to define the actions thatshould be carried out in order to guarantee the expected conditions of survival, growth and sustained profitability. Such decisions ar madeunder uncertainty, since future external and internal conditions are unknown. The prospective studies intend to identify future and potential business scenarios to reduce uncertainty conditions in order to assume decisions with the highest probability of success for the organization.